Multi-objective optimisation of the cure of thick components - Struzziero, Giacomo; Skordos, Alexandros A. (Cranfield University, 2016)
The file-set contains the following files: - Flatpanel_24mm.dat: A Marc input file used as template for the optimisation methodology - Usub.f: Contains the subroutines implemented to modify the input file at each optimisation iteration - Exhaustive_search.xlsx: Contains the data of the comparison between the GA and exhaustive search final Pareto fronts. Columns contain temperature of first and second dwell, duration of first dwell, ramp rate, process time and overshoot temperature for the exhaustive case whilst in column H and I the process time and overshoot temperature of the GA Pareto are reported. - Flat_panel_results.xlsx: The spreadsheet contains: optimisation of flat panel 24 and 60 mm case, optimisation of flat panel 60 mm with 30 and 100 W/m^2 K convection coefficient and optimisation of flat panel 24 mm with 30 and 100 W/m^2 K convection coefficient. In each sheet columns contain the generation number, the optimisation parameters, process time and temperature overshoot. - L_shape_results.xlsx: The spreadsheet contains optimisation of the L-shape for the 24 and 60 mm case. In each sheet columns contain the generation number, the optimisation parameters, process time and temperature overshoot. - T_joint_results.xlsx: The spreadsheet contains optimisation of the T-joint for the 24 and 60 mm case. In each sheet columns contain the generation number, the optimisation parameters, process time and temperature overshoot. - L_shape_24mm_corner_point.xlsx: Contains the detailed analysis of a corner point optimisation solution for the L-shape 24 mm. Columns contain time, temperature, degree of cure and reaction rate values at different increments for different nodes through thickness. - L_shape_24mm_standard_point.xlsx: Contains the detailed analysis of the standard point solution for the L-shape 24 mm. Columns contain time, temperature, degree of cure and reaction rate values at different increments for different nodes through thickness. - L_shape_24mm_horizontal_point.xlsx: Contains the detailed analysis of a corner point optimisation solution for the L-shape 24 mm. Columns contain time, temperature, degree of cure and reaction rate values at different increments for different nodes through thickness.
Keywords: Composite materials; Manufacturing Processes; Numerical Analysis; Finite Element Analysis; Cure; Aerospace Engineering; Aerospace Materials; Optimisation; Manufacturing Processes and Technologies (excl. Textiles)